Supportive Social Interactions in Infertility Treatment Decrease Cortisol Levels: Experimental Study Report - Malina, Alicja; Głogiewicz, Małgorzata; Piotrowski, Jakub (Frontiers in Psychology, 2019)
Purpose: The aim of the research project was to analyze the importance of supporting social interactions in the process of infertility treatment. In Poland, where the study was conducted, the acceptance of ART (Assisted Reproductive Technology) methods is still lower than in western Europe countries; therefore, the social stigma of infertility exists. The research project draws attention to the issue of disclosure of fertility problems and the ability to seek support, which is a problem for many Polish couples. Methods: The study was conducted in an experimental model. Fifty one heterosexual couples qualified for IVF were recruited to take part in the study. The participants were randomly divided between the experimental and control group. The first stage of the research procedure was carried out with all the couples. It included taking a saliva sample to obtain information about the level of stress based on the cortisol test. In the second stage the control group watched a non-emotional video about human embryology. The other half of participants- couples undergoing infertility treatment were subject to a supportive social interaction. The interaction was conducted in 5 separate groups- 5 couples each and was a regular conversation about the couples’ hopes and fears. After introducing the experimental and control condition a saliva sample was again collected from all participants. An information about the history of infertility treatment was also collected. Results and conclusion: The statistical analysis indicates a significant decrease in the level of stress experienced after the supportive social interaction. The results of the analysis of differences between the experimental group and the control group showed a larger decrease of cortisol level among women and men.